Less loop diuretic use in patients on sacubitril/valsartan undergoing remote pulmonary artery pressure monitoring. (4th November 2021) - Böhm, Michael; Assmus, Birgit; Anker, Stefan D.; Asselbergs, Folkert W.; Brachmann, Johannes; Brett, Marie‐Elena; Brugts, Jasper J.; Ertl, Georg; Wang, AiJia; Hilker, Lutz; Koehler, Friedrich; Rosenkranz, Stephan; et al.
Abstract: Aims: Control of pulmonary pressures monitored remotely reduced heart failure hospitalizations mainly by lowering filling pressures through the use of loop diuretics. Sacubitril/valsartan improves heart failure outcomes and increases the kidney sensitivity for diuretics. We explored whether sacubitril/valsartan is associated with less utilization of loop diuretics in patients guided with haemodynamic monitoring in the CardioMEMS European Monitoring Study for Heart Failure (MEMS‐HF). Methods and results: The MEMS‐HF population ( n = 239) was separated by the use of sacubitril/valsartan ( n = 68) or no use of it ( n = 164). Utilization of diuretics and their doses was prespecified in the protocol and was monitored in both groups. Multivariable regression, ANCOVA, and a generalized linear model were used to fit baseline covariates with furosemide equivalents and changes for 12 months. MEMS‐HF participants ( n = 239) were grouped in sacubitril/valsartan users [ n = 68, 64 ± 11 years, left ventricular ejection fraction (LVEF) 25 ± 9%, cardiac index (CI) 1.89 ± 0.4 L/min/m 2 ] vs. non‐users ( n = 164, 70 ± 10 years, LVEF 36 ± 16%, CI 2.11 ± 0.58 L/min/m 2, P = 0.0002, P < 0.0001, and P = 0.0015, respectively). In contrast, mean pulmonary artery pressure (PAP) values were comparable between groups (29 ± 11 vs. 31 ± 11 mmHg, P = 0.127). Utilization of loop diuretics was lower in patients taking sacubitril/valsartan compared with those without ( P = 0.01). Significant predictor of loop diuretic use was a history of renal failure ( P = 0.005) but not age ( P = 0.091). After subjects were stratified by sacubitril/valsartan or other diuretic use, PAP was nominally, but not significantly lower in sacubitril/valsartan‐treated patients (baseline: P = 0.52; 6 months: P = 0.07; 12 months: P = 0.53), while there was no difference in outcome or PAP changes. This difference was observed despite lower CI ( P = 0.0015). Comparable changes were not observed for other non‐loop diuretics ( P = 0.21). Conclusions: In patients whose treatment was guided by remote PAP monitoring, concomitant use of sacubitril/valsartan was associated with reduced utilization of loop diuretics, which could potentially be relevant for outcomes.